2007
DOI: 10.1586/14789450.4.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation site analysis of the anti-inflammatory and mRNA-destabilizing protein tristetraprolin

Abstract: Tristetraprolin (TTP) is a member of the CCCH zinc finger proteins and is an anti-inflammatory protein. Mice deficient in TTP develop a profound inflammatory syndrome with erosive arthritis, autoimmunity and myeloid hyperplasia. TTP binds to mRNA AU-rich elements with high affinity for UUAUUUAUU nucleotides and causes destabilization of those mRNA molecules. TTP is phosphorylated extensively in vivo and is a substrate for multiple protein kinases in vitro. A number of approaches have been used to identify its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 83 publications
(171 reference statements)
3
49
0
Order By: Relevance
“…TTP has the potential to be phosphorylated at a number of residues by various kinases (6,7,13), and inhibition of PP2A results in dramatic hyperphosphorylation of TTP (Fig. 6) (57).…”
Section: Discussionmentioning
confidence: 99%
“…TTP has the potential to be phosphorylated at a number of residues by various kinases (6,7,13), and inhibition of PP2A results in dramatic hyperphosphorylation of TTP (Fig. 6) (57).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TTP, a human protein of the TIS11 family, induces the degradation of ARE-containing mRNAs through a large variety of mechanisms including deadenylation, decapping, and P-body targeting. Sequence alignment of TIS11 family members reveals a high degree of conservation in the CCCH zing finger RNA-binding region (34), whereas other regions of the protein are poorly conserved between invertebrates and mammals, suggesting that the molecular mechanism controlling the activity of TIS11 proteins may have evolved in the course of eukaryotic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…4, 3, lanes 1 and 5). These results demonstrate that AUF1p45 can bind to all known mammalian TTP family members, presumably reflecting the high degree of amino acid conservation in their TZF domains (38,39).…”
Section: B1 Lane 2 and B2 Lane 2) And In Igg Immunoblotsmentioning
confidence: 78%